(untitled) (Philological Studies, 2020)
The article presents the authors of literary creation, based on the theory of Julia Kristeva Tales of Love, 1987 and Marie Nikolajave Reading for Learning, 2015. Trial is the author of medieval trobairitz, enlightenment préciosité, romantic women fairy tale writers to contemporary trobairitz. The texts of the authors of the intertextual, dominated by emotional motifs (love, trust, loyalty), supported by actions (Love test) reflect the symbols (garden fountain, wall). Central emotional ekphrasis - love the emotion that has similar symptoms as anxiety (expectation, call and meeting). The authors express themselves with metaphors, often as literary parallelism - externalization of the inner landscape - literal and emotional winter. The authors are suggestible translate visuals into verbal world - songs (Azalais de Porcairagues, Comtessa de Dia, Maria de Ventadorn), memories (Helena Kottanner), fairy tales (Jeanne Marie Leprince de Beaumont).